Utilization of rice and mungbean in chicken nuggets - Mella, Flomella Arevalo
The study was conducted in four phase. Phase I involved the development of the composition and procedure for chicken for nuggets.In Phase II,different mungbean preparations (boiled, sprout and flour) were mixed with rice flour, in a 30:70 ratio and was used to partially substitute the chicken in the formulation to determine the most acceptable mungbean preparation. The levels of substitution used were 30, 40 and 50%. In Phase III, the optimum amount of the mixture of the most acceptable mungbean preparation and rice flour was determined.The levels of substitution used were ar 0, 25, 50, 75 and 100%. Phase IV involved the validation of the optimum preparation and its comparison with a commercial sample. In Phase II to IV, consumer acceptability test of the product with 24 to 60 panelists using 15-cm unstructured line scales. The most acceptable mungbean preparation was found to be sprouts which can be used until the 50% level of substitution. Further optimization of the formulation using mungbean sprouts indicated that the use of up to 75% level of substitution still produced chicken nuggets that were acceptable to consumers.